PEMBERDAYAAN MASYARAKAT PENGELOLA OBYEK WISATA PANTAI HARLEM DI KAMPUNG TABLASUPA OLEH DINAS KEBUDAYAAN DAN PARIWISATA KABUPATEN JAYAPURA - Mulyana Mulyana; Evan Stanley Siby (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2020)
Harlem Beach is one of the tourist objects in Jayapura Regency which has the potential to improve the welfare of the people of Tablasupa Village. This study aims to determine an overview of the community empowerment efforts of Harlem Beach managers based on their potential. This research uses descriptive qualitative method with an inductive approach. The data collection techniques used by the author are unstructured interviews using outlines of the problem, observation, documentation and triangulation of data sources. Data analysis techniques using data reduction, data presentation, and drawing conclusions. An interesting finding in this conclusion is that the empowerment of the community managing Harlem Beach tourism objects by the Jayapura Regency Culture and Tourism Office uses the AGIL concept by building facilities, providing skills training and carrying out promotions but is still constrained by issues of customary rights, limited facilities and infrastructure. The conclusion of this study is that the empowerment efforts carried out based on the AGIL concept are considered to be not optimal, because they are hampered by several factors such as lack of facilities, poor infrastructure, unclear customary rights, lack of capital, the absence of BUMKAM and a lack of community mindset. Keywords: empowerment, community, beach tourism